EP.TH.961Meta-analysis of Spinal Anaesthesia Versus General Anaesthesia During Laparoscopic Total Extraperitoneal Repair of Inguinal Hernia. (28th October 2021) - Hajibandeh, Shahin; Hajibandeh, Shahab; Mobarak, Shahd; Mobarak, Dham; Satyadas, Thomas
Abstract: Objectives: To evaluate comparative outcomes of spinal anaesthesia (SA) and general anaesthesia (GA) during laparoscopic total extraperitoneal (TEP) repair of inguinal hernia. Methods: We systematically searched MEDLINE; EMBASE; CINAHL; CENTRAL, and bibliographic reference lists. Post-operative pain assessed by visual analogue scale (VAS), individual and overall perioperative morbidity, procedure time and time taken to normal activities, were the outcome parameters. Combined overall effect sizes were calculated using fixed-effect or random-effects models. Results: We identified 5 studies enrolling 1, 518 patients (2, 134 hernia) evaluating outcomes of laparoscopic TEP repair under SA (n = 1, 277 patients, 1, 877 hernia) or GA (n = 241 patients, 257 hernia). SA was associated with significantly lower post-operative pain assessed by VAS at 12 hours (MD: - 0.32, P < 0.0001) and shorter time to normal activities (MD: -0.30, P = 0.002) compared to GA. However, it significantly increased risk of urinary retention (OR:4.02, P = 0.01), hypotension (OR:3.97, P = 0.004), headache (OR:7.65, P = 0.003), and procedure time (MD: 3.82, P = 0.004) There was no significant difference in VAS at 24 hours (MD:0.06, P = 0.34), seroma (OR:1.54, P = 0.26), wound infection (OR:1.03, P = 0.94), and vomiting (OR:0.84, P = 0.66) between two groups. There was a non-significant decrease in overall morbidity in favour GA (OR:1.84, P = 0.17) which became significant following sensitivity analysis (OR:2.59, P = 0.01). Conclusions: Although TEP inguinal hernia repair under SA may reduce pain in early postoperative period, it seems to be associated with increased postoperative morbidity and longer procedure time. It may be an appropriate anaesthetic modality in selected patients who are considered high risk for GA. Higher level of evidence is needed.